Effects of Extra Judicial Measures on Journalists by Nigerian Government - Nwonu, Clifford O. (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
The watch-dog role of the press demands that the press be given freedom to hunt for information and disseminate same to the public. With the Nigerian government waiting to bounce on the media at the slightest opportunity, there is no how the journalists can fix their eyes on the executive, legislature and judiciary to ensure that they do not abuse their power and to fish out corrupt ones among the leaders. In order to do justice to this topic the researcher set out to discover practical cases of different measures used against the press by the government. Books, journals, and other documents were the secondary data used to uncover these facts. At the end, it was discovered that despite the dehumanizing treatment meted out to the Nigerian press by the civilian and military governments, it still remains the most vibrant and outspoken sector in the whole of Africa. Some recommendations were made among; which are that the government should give the press freedom and adequate security; and that the press should discharge its duty bearing in mind the ethics of journalism which encourage it to be fair, accurate and objectives.